2018
DOI: 10.1007/s00425-018-2862-5
|View full text |Cite
|
Sign up to set email alerts
|

Phytoglobins regulate nitric oxide-dependent abscisic acid synthesis and ethylene-induced program cell death in developing maize somatic embryos

Abstract: During maize somatic embryogenesis, suppression of phytoglobins (Pgbs) reduced ABA levels leading to ethylene-induced programmed cell death in the developing embryos. These effects modulate embryonic yield depending on the cellular localization of specific phytoglobin gene expression. Suppression of Zea mays phytoglobins (ZmPgb1.1 or ZmPgb1.2) during somatic embryogenesis induces programmed cell death (PCD) by elevating nitric oxide (NO). While ZmPgb1.1 is expressed in many embryonic domains and its suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…ABA is a positive regulator of the senescence process, and ABA levels increase in senescing leaves, which is accompanied by the increased expression of the genes encoding the key enzymes involved in ABA biosynthesis [ 80 , 81 ]. In maize, the appropriate onset and progression of PCD in the endosperm depend on the balance between ABA and ethylene; treating the wild type with an inhibitor of ABA biosynthesis phenocopied ABA-deficient mutants, including an increase in ethylene production and accelerated execution of PCD [ 82 ].…”
Section: Factors Regulating Plant Pcdmentioning
confidence: 99%
“…ABA is a positive regulator of the senescence process, and ABA levels increase in senescing leaves, which is accompanied by the increased expression of the genes encoding the key enzymes involved in ABA biosynthesis [ 80 , 81 ]. In maize, the appropriate onset and progression of PCD in the endosperm depend on the balance between ABA and ethylene; treating the wild type with an inhibitor of ABA biosynthesis phenocopied ABA-deficient mutants, including an increase in ethylene production and accelerated execution of PCD [ 82 ].…”
Section: Factors Regulating Plant Pcdmentioning
confidence: 99%
“…Physiological work using transgenic plants with altered concentrations of Glbs has shown that these proteins play an important role in plant development and morphogenesis, and largely supports the theory that they do so by modulating NO concentrations (Hill, ; Hebelstrup et al , ). Glbs may act through NO modulation to affect the signaling pathways of hormones including auxins (Elhiti et al , ), cytokinins (Ross et al , ; Wang et al , ), salicylate (Mur et al , ), jasmonates (Mur et al , ; Mira et al , ), ethylene (Mur et al , ; Kapoor et al , ; Hartman et al , ) and abscisic acid (ABA; Kapoor et al , ; Rubio et al , ). Two exemplary studies, concerning the response of Arabidopsis to biotic and abiotic stress, will illustrate the triple crosstalk between Glbs, hormones and NO.…”
Section: Globins Of Angiospermsmentioning
confidence: 99%
“…SCW-and PCD-related cis-elements were also found upstream of PhAP57.1, − 57.2 and − 57.3 ( Figure S1). To date, methyl jasmonate (MeJA)-, gibberellin (GA)-, ABA-, and ethylene-related as well as MYB transcription factors have been reported to be involved in PCD [58][59][60]. Hence, these results suggested that PhAPs may be potentially involved in SCW and PCD processes.…”
Section: Cis-element Analysis Of Phap Family Genesmentioning
confidence: 98%